From Planning to Management of Cultural Heritage Sites: Controversies and Conflicts Between Unesco WHL Management Plans and Local Spatial Planning in South-Eastern Sicily - Piccolo, Francesco Lo; Todaro, Vincenzo (European Spatial Research and Policy, 2015)
The paper investigates the relationship between the preservation of cultural heritage and planning in UNESCO World Heritage List (WHL) sites, with special reference to the relation between Management Plans and other (local and regional) planning instruments and policies able to influence the promotion of sustainable and responsible development. This will be explored through a case study related to South-Eastern Sicilian UNESCO sites (in particular Syracuse). The analysis of this case study will point out the challenge of integrating different management and planning regimes - which mainly refer to a performative model - in a (still) very conformative planning system. The paper will show how supranational protection tools and models often lose their efficacy in relation to local planning systems.